From pictures to words: Introducing young learners’ vocabulary at TK Al-Qur'an Ulfa Padangsidimpuan - Wildan Iskandar Lubis; Lollo Rosa Lubis; Aulia Fitrah Ananda Ritonga; Diah Nanda Amelia Siregar; Fadillah Nursakinah; Indah Wulan Safitri; Kiky Aryani; Lelawani Hutasuhut; Lufiah Hutasuhut; Poppy Nurianda (CV. Yudhistt Fateeh, 2026)
This community service activity aimed to improve English vocabulary mastery among early childhood learners at TK Al-Qur’an Ulfa through the From Pictures to Words approach. The activity employed a Learning by Playing method utilizing visual media (flashcards) and audio media (songs), focusing on vocabulary related to colors and fruits. A pre-test and post-test design was used to evaluate students’ vocabulary improvement. The participants consisted of 30 kindergarten students. The results indicated a substantial increase in students’ vocabulary mastery, with the mean score improving from 53.13 in the pre-test to 75.63 in the post-test, resulting in a mean gain of 22.50 points. The paired-sample t-test analysis revealed a statistically significant difference between pre-test and post-test scores (t = 195.70, df = 29, p < .05), indicating that the intervention had a significant positive effect on students’ learning outcomes. Furthermore, the N-Gain score was 0.487 (48.7%), which falls into the moderate improvement category. In addition to the quantitative findings, students demonstrated high levels of enthusiasm and active participation throughout the learning process. These findings suggest that the integration of visual and audio media through the From Pictures to Words approach is effective in enhancing English vocabulary mastery and engagement among young learners.